Regulation of new markets in telecommunications? Market dynamics and shrinking monopolistic bottlenecks - Charles B. Blankart; Günter Knieps; Patrick Zenhäusern (Albert-Ludwigs-Universität Freiburg, Institut für Verkehrswissenschaft und Regionalpolitik, 2007)
This paper aims at localizing network-specific market power in new markets. Three kinds of transmission qualities on service markets can be differentiated according to the products provided: narrowband services like PSTN/ISDN or GSM, semi high-speed broadband services like broadband internet access up to 6 Mbps download and VDSL services up to 50 Mbps. As long as, due to the absence of alternative network infrastructures, a monopolistic bottleneck in local infrastructure networks exists the question arises what the remaining bottleneck components are for these different markets. In this paper the shrinking-bottleneck hypothesis will be demonstrated.
Older version: http://hdl.handle.net/10419/32315
Keywords: 330; Telekommunikationspolitik; Breitbandkommunikation; Netzzugang; Monopol; Bottleneck; EU-Staaten